ЗАСОБИ РОЗРАХУНКУ ТА ВИБОРУ УСТАВОК ДИФЕРЕНЦІЙНО-ФАЗНОГО ЗАХИСТУ ПОВІТРЯНИХ ЛІНІЙ МІКРОПРОЦЕСОРНИХ ЗАХИСТІВ L60 В СКЛАДНИХ ЕЛЕКТРИЧНИХ МЕРЕЖАХ ДО 10 000 ВУЗЛІВ - Блінов, І.В.; Колесникова, Н.Ф.; Козлова, О.І. (Інститут електродинаміки Національної академії наук України, 2024)
The means for calculation and selection of phase-differential protection settings of overhead lines of L60 microprocessor protections of the General Electric company in complex electrical networks up to 10,000 nodes was developed. This software allows to select settings according to the possible types of mixed signals: forward-sequenced and reverse-sequenced, as well as additional criteria. The program makes it possible to check the sensitivity of the starting and disconnecting devices in the case of symmetrical and asymmetrical short circuits, in the case of maximum reverse power flows in various mixed starts. Ref. 3 fig. 5.